OPTIMALISASI POTENSI LOKAL MELALUI PROGRAM PEMBERDAYAAN MASYARAKAT DALAM PEMANFAATAN DAN PENGOLAHAN LELE (Clarias sp.) DI KAMPUNG KB “GEMA KENCANA” - Muhammad Nuzul Azhim Ash Siddiq; Fahrul Rozi; Venna Sinthary; Chaidir Masyhuri Majiding (Universitas Mataram, 2026)
Catfish (Clarias sp.) is a local commodity with high nutritional and economic potential that has not been optimally utilized by the community in Kampung KB “Gema Kencana”, Sindang Sari. The main partners, a group of women, possess a strong entrepreneurial spirit but face limitations in nutritional knowledge and skills for processing catfish into value-added products. This gap hinders local economic development and the full realization of nutritional benefits for stunting prevention. This community service activity aimed to increase partners' knowledge of the nutritional value of catfish and to train their skills in processing catfish into fish floss and crackers. The implementation method used a participatory approach consisting of three stages: a situational analysis survey, education with a pre-test and post-test, and hands-on training (learning by doing) targeting 24 women members of Kampung KB “Gema Kencana”. The results showed a statistically significant increase in knowledge (p<0.001), with the average participant score rising from 67.50 to 83.33. During the training session, all participants showed high enthusiasm and successfully practiced their new skills by producing good-quality catfish floss and crackers. The program successfully transformed the partners' understanding and abilities from mere consumers to potential producers. Therefore, this empowerment program proved effective in enhancing both the knowledge and practical skills of the participants, in line with the established objectives.